2023
DOI: 10.1007/s13555-023-00977-1
|View full text |Cite|
|
Sign up to set email alerts
|

Matching-Adjusted Indirect Comparison of the Long-Term Efficacy of Deucravacitinib Versus Adalimumab for Moderate to Severe Plaque Psoriasis

April W. Armstrong,
Sang Hee Park,
Vardhaman Patel
et al.

Abstract: Introduction Deucravacitinib, an oral tyrosine kinase 2 (TYK2) inhibitor, is approved in the United States to treat adults with moderate-to-severe plaque psoriasis (PsO). This study compared the long-term efficacy of deucravacitinib and adalimumab using results from long-term extension (LTE) trials. Methods Open-label LTE trials were identified for an indirect treatment comparison (deucravacitinib: POETYK PSO-LTE [NCT04036435]; adalimumab: REVEAL extension [NCT00195676]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The first small molecule TYK2 inhibitor was approved by the FDA in 2022 for the treatment of psoriasis, with additional agents under investigation for use in other autoimmune conditions (57)(58)(59). TYK2 mediates signaling through several cytokines that have been linked with T1D pathogenesis, including IFNα, IL-12, and IL-23.…”
Section: Discussionmentioning
confidence: 99%
“…The first small molecule TYK2 inhibitor was approved by the FDA in 2022 for the treatment of psoriasis, with additional agents under investigation for use in other autoimmune conditions (57)(58)(59). TYK2 mediates signaling through several cytokines that have been linked with T1D pathogenesis, including IFNα, IL-12, and IL-23.…”
Section: Discussionmentioning
confidence: 99%
“…At long-term follow-up (44–60 weeks), deucravacitinib PASI75 was 65.9% (58.0–73.4), also close to the PASI75 achieved by first-generation biologics adalimumab 62.8% (55.3–69.6) and ustekinumab 68.0% (64.6–71.5). Furthermore, a matching-adjusted indirect comparison (MAIC) of the long-term efficacy of deucravacitinib versus adalimumab for patients with moderate-to-severe plaque psoriasis was recently published [ 47 ]. This MAIC concluded that patients treated with deucravacitinib showed a higher long-term response rate at 2 years than with adalimumab.…”
Section: Emerging Oral Treatments For Psoriasismentioning
confidence: 99%
“…3-69.6) and ustekinumab 68.0% (64.6-71.5). Furthermore, a matching-adjusted indirect comparison (MAIC) of the long-term efficacy of deucravacitinib versus adalimumab for patients with moderate-to-severe plaque psoriasis was recently published [47]. This MAIC concluded that patients treated with deucravacitinib showed a higher long-term response rate at 2 years than with adalimumab.…”
Section: Deucravacitinibmentioning
confidence: 99%